Abdominal coarctation in a hypertensive female collegiate basketball player. Issue 5 (23rd September 2004) - Sloan, B; Simons, S; Stromwall, A
Abstract : The purpose of the preparticipation examination is to identify health conditions that might adversely affect an athlete while participating in sport. Hypertension is the most common. This case report details a female basketball player found to be hypertensive, and complaining of fatigue, at her preparticipation physical examination. Presentation, diagnostics, treatment, and final outcome of coarctation involving the abdominal aorta are summarised.